Effect of Work Quality On Employee Performance In PT. Summa Logistics Nusantara - Nurlaelah, Nurlaelah; Rizal S, Muh; Aslinda, Andi; Akib, Haedar; Nur, Andi Cudai (Pinisi Business Administration Review, 2024)
This research examines the influence ofWork Quality on Employee Performance at PT. Summa Logistics Nusantara. The purpose of this study was to determine the level ofquality of work of employees at PT. Summa Logistics Nusantara, to know the performanceemployees at PT. Summa Logistics Nusantara, and to find out the magnitude of the effectwork quality on employee performance at PT. Summa Logistics Nusantara. This research approach is quantitative. This research was carried outinPT. Summa Logistics Nusantara. Sources of data in the study areemployee atPT. Summa Logistics Nusantarain March to April 2022. Data collection techniques in the form of observation, questionnaires / questionnaires and documentation. Data analysis techniques in the form of validity test, reliability test, normality test, descriptive analysis, simple linear regression analysis, correlation coefficient analysis, and analysis of the coefficient of determination. The results of the study indicate that the indicators used in each of these variables indicate where the work quality of employees is in the very good category. Indicators on employee performance variables are in the very good category. Based on the correlation test, there is a very strong relationship between the two variables. It can be concluded that there is an influence between work quality on employee performance inPT. Summa Logistik Nusantara.